Syncretic Beliefs and Practices amongst Christians in Nigeria: Causes and Way Forward - Deborah Oluwaseun Jegede; Sunday Noah Onaolapo; Niyi Jacob Ogunode (Researchparks Publishing, 2023)
This paper discussed the factors responsible for syncretic beliefs and practices amongst Christians in Nigeria. Secondary data were adopted in the paper. The data were collected from published and unpublished articles. The paper identified protection, power, childbearing, healing and deliverance, unfulfilled needs, miracles, a policy of religious tolerance and materialism as causes of syncretic beliefs and practices amongst Christians in Nigeria. To address and solve this problem, the paper hereby recommended that Church leaders in Nigeria should openly discourage members from engaging in syncretic practices, and should be enlightened on the effects of such engagements. They should be encouraged to trust and wait patiently in the almighty God as the source of their helps as Christians